CFD simulations of transport phenomena during transcritical flow of real fluid (CO2) within ejector. Issue 3 (3rd May 2016) - Nowak, Andrzej J; Palacz, Michal; Smolka, Jacek; Banasiak, Krzysztof; Bulinski, Zbigniew; Fic, Adam; Hafner, Armin
Abstract : Purpose: – The purpose of this paper is to overview successful approaches to the computational simulation of real fluid (R744 – carbon dioxide (CO2 )) flow within an ejector is presented. Important issues such as the ejector geometry and its optimisation, the adapted equations of state and the proposed models of the process, fluid parameters, etc., are examined and critically discussed. Whenever possible, the discussed models are experimentally validated. In the conclusion, some trends in future research are pointed out. Design/methodology/approach: – Flow within CO2 ejector is generally transcritical and compressible. Models existing in the literature are shortly described and critically compared. Whenever possible, those models were validated against the experimental data. In a model validation process, the primary and secondary mass flow rates as well as the pressures at the selected points in the mixing section and diffuser were compared, showing a satisfactory agreement between experimental and computational results. Findings: – Developed CO2 ejector flow models are tested in few industrial applications. All these initiatives bring solutions which are interesting and very promising from technological point of view. Originality/value: – This is an extensive overview of successful approaches to computational simulation of the real fluid (R744 – CO2 ) flow within ejector. It brings many useful information.